2008
DOI: 10.1016/j.virusres.2007.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel viral interleukin-10 isoforms of human cytomegalovirus AD169

Abstract: Two products of human cytomegalovirus (HCMV) UL111a gene have been previously identified to resemble human IL-10 (hIL-10). These viral IL-10s (vIL-10s) are able to induce signal transduction events and biological activities in a variety of cells. In this study, five novel vIL-10 transcripts were identified from HCMV AD169 infected MRC-5 cells. Some vIL-10 isoforms were posttranslationally glycosylated, depending on the existence of a predicted N-linked glycosylation site. Similar to hIL-10, four of the vIL-10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 41 publications
3
44
1
Order By: Relevance
“…14 Transcripts predicted to encode LAcmvIL-10 have also been detected during productive infection of human foreskin fibroblasts (HFs), 39 as have several additional viral IL-10 variants. 40 The detection of LAcmvIL-10 transcription during latent infection raised the possibility that LAcmvIL-10 may encode similar immunosuppressive properties to cmvIL-10. However, analysis of cells treated with recombinant LAcmvIL-10 protein demonstrated that its immunosuppressive properties are more restricted than those of cmvIL-10 as the only function reported to date has been the ability to down-regulate MHC class II on myeloid cells.…”
Section: Introductionmentioning
confidence: 99%
“…14 Transcripts predicted to encode LAcmvIL-10 have also been detected during productive infection of human foreskin fibroblasts (HFs), 39 as have several additional viral IL-10 variants. 40 The detection of LAcmvIL-10 transcription during latent infection raised the possibility that LAcmvIL-10 may encode similar immunosuppressive properties to cmvIL-10. However, analysis of cells treated with recombinant LAcmvIL-10 protein demonstrated that its immunosuppressive properties are more restricted than those of cmvIL-10 as the only function reported to date has been the ability to down-regulate MHC class II on myeloid cells.…”
Section: Introductionmentioning
confidence: 99%
“…Only a subset of viral genes are transcriptionally active during latency (2,8,12,13,17,23,34,47), including HCMV UL111A, a gene that encodes homologs of the potent immunomodulatory cytokine human interleukin-10 (hIL-10). UL111A is transcriptionally active during both productive and latent phases of infection and encodes several viral IL-10 proteins (17,(24)(25)(26)46) which exert a diverse range of immunomodulatory functions, including inhibition of cytokine synthesis and major histocompatibility complex (MHC) expression by myeloid cells, stimulation of B cells, and suppression of DC maturation and cytotrophoblast function (5-7, 9, 16, 18, 36, 51, 52, 61). The vast majority of characterization of functions has come from studies using recombinant viral IL-10 proteins, although some have also assessed function during productive infection with viruses with deficient viral IL-10 proteins.…”
mentioning
confidence: 99%
“…Additional studies have shown that cmvIL-10 can inhibit NF-B signaling in monocytes (Nachtwey and Spencer, 2008). Like human IL-10, the cmvIL-10 protein forms a dimer, and evidence suggests that cmvIL-10 can form heterodimers with human IL-10 that actually enhance Stat3 phosphorylation (Lin et al, 2008). receptor.…”
Section: Cell Signalingmentioning
confidence: 99%